Pengaruh Profesionalisme Kerja Dan Lingkungan Kerja Terhadap Efektivitas Kerja Pegawai Di Kantor Kelurahan Koja Jakarta Utara - Ain, Eima Zahroti; Chaerunisyah, Ana (Jurnal Ilmu Administrasi Publik, 2024)
In order to achieve quality effectiveness, it is necessary to be supported by the professionalism of its employees and the environment in which the employees work. To foster the effectiveness of employee work, leaders must pay attention to several aspects, namely employee professionalism and work environment. This study aims to analyze how much influence work professionalism and work environment have on employee work effectiveness at the Koja Village Office. This study uses a quantitative research method. The population in this study were all 20 Koja Village employees, the sampling technique used a saturated sampling technique. The data collection techniques in this study were primary data and secondary data. The results of the study showed that: (1) work professionalism has a positive and significant effect of 56.2% on work effectiveness with a significance value of <0.001 (2) the work environment has a positive and significant effect of 39.5% on work effectiveness with a significance value of 0.003 (3) work professionalism and work environment have a positive and significant effect of 58.3% on work effectiveness with a significance value of <0.001. The better the work professionalism and work environment, the better the employee work effectiveness.